2017
DOI: 10.1038/s41598-017-08915-w
|View full text |Cite
|
Sign up to set email alerts
|

Chemically imaging bacteria with super-resolution SERS on ultra-thin silver substrates

Abstract: Plasmonic hotspots generate a blinking Surface Enhanced Raman Spectroscopy (SERS) effect that can be processed using Stochastic Optical Reconstruction Microscopy (STORM) algorithms for super-resolved imaging. Furthermore, by imaging through a diffraction grating, STORM algorithms can be modified to extract a full SERS spectrum, thereby capturing spectral as well as spatial content simultaneously. Here we demonstrate SERS and STORM combined in this way for super-resolved chemical imaging using an ultra-thin sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 69 publications
0
36
0
Order By: Relevance
“…A framework satisfying these criteria was recently developed by Earle et al [ 58 ], where high-resolution quantification of the spatial organization of the gut microbiome revealed that changes in the proximity of microbes to the epithelium are sufficient to induce increased expression of key inflammatory markers, despite negligible shifts in microbiota composition. Most recently, chemical imaging techniques exploiting a blinking surface enhanced Raman spectroscopy (SERS) have been used to visualize bacteria in vitro with exquisite resolution, and have demonstrated the ability to differentiate between the chemical signatures of different bacteria [ 59 ]. MRI, CT, fluorescence/bioluminescence imaging, and PET have also been applied to investigate the activity of bacteria in vivo; however, these typically only provide indirect information about bacterial activity by inference from immune function [ 60 , 61 ].…”
Section: Pet and Spect Of Specific Mediators In Ibdmentioning
confidence: 99%
“…A framework satisfying these criteria was recently developed by Earle et al [ 58 ], where high-resolution quantification of the spatial organization of the gut microbiome revealed that changes in the proximity of microbes to the epithelium are sufficient to induce increased expression of key inflammatory markers, despite negligible shifts in microbiota composition. Most recently, chemical imaging techniques exploiting a blinking surface enhanced Raman spectroscopy (SERS) have been used to visualize bacteria in vitro with exquisite resolution, and have demonstrated the ability to differentiate between the chemical signatures of different bacteria [ 59 ]. MRI, CT, fluorescence/bioluminescence imaging, and PET have also been applied to investigate the activity of bacteria in vivo; however, these typically only provide indirect information about bacterial activity by inference from immune function [ 60 , 61 ].…”
Section: Pet and Spect Of Specific Mediators In Ibdmentioning
confidence: 99%
“…Lindquist's group 149 combined SERS direct detection with STORM by a 700 nm hexagonal periodic metal nanopore SERS hotspot array with a unit diameter of 150 nm to match a 660 nm laser, which causes the hotspot scintillation locating at 10 nm regions of the substrate to achieve the SERS-STORM imaging. They further employed an ultrathin silver island film to identify the molecular structures of the cell walls of two types of bacteria (Gram-negative bacteria and Gram-positive bacteria) 150 . So far, there are no reports on SERS supra-resolution imaging to visualize the distributions of intracellular compartments with the help of SERS tags.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a technique employing stochastic optical reconstruction microscopy (STORM) algorithms was used to process SERS spectra, enabling chemical‐specific, super‐resolution images . The spatial location of SERS “hot‐spots” were dynamically shifted over nanohole arrays or roughened Ag films with subdiffraction‐limited resolution using a spatial light modulator . The dynamically shifted SERS “hot‐spots” generated “blinking” events where SERS spectral information was collected.…”
Section: Bacterial Imaging/mapping With Sersmentioning
confidence: 99%
“…Over the timescale of minutes, about 4000 frames of SERS “blinking” events were collected, and processed with STORM to generate an image. SERS‐STORM images were collected for B. subtilis , E. coli , and M. luteus , and compared against conventional diffraction‐limited SERS and SEM imaging . Excellent agreement between the SEM and SERS‐STORM images was observed.…”
Section: Bacterial Imaging/mapping With Sersmentioning
confidence: 99%